2022
DOI: 10.1039/d2ra01033j
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent HAT/ET mechanism of the reaction of phenols with 2,2-diphenyl-1-picrylhydrazyl (dpph˙) in methanol

Abstract: Concentration dependent contribution of hydrogen atom transfer and electron transfer to the overall kinetics of reaction of phenols with a 2,2-diphenyl-1-picrylhydrazyl radical in methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Other authors have found a significant correlation between the antioxidant activity and total phenolic content in the albumin protein fraction in wheat [56]. The decrease in DPPH scavenging capacity of the WG HP-BP fraction, in relation to the low-and medium-protein grains (WG LP and WG MP), may be due to alteration in the mechanism of reaction in the DPPH method due to changes in phenolic concentration, as has been suggested previously [71]. Most of the phenolic compounds are located in the wheat bran layer covalently crosslinked with the cell wall polymers [49,69]; the phenolic content ratio in bran, as compared to germ, is 15-to 18-fold, as has been reported previously, and in agreement with different authors, this correspond mostly to phenolic acids [70].…”
Section: Total Antioxidant Capacity (Tac)supporting
confidence: 65%
See 1 more Smart Citation
“…Other authors have found a significant correlation between the antioxidant activity and total phenolic content in the albumin protein fraction in wheat [56]. The decrease in DPPH scavenging capacity of the WG HP-BP fraction, in relation to the low-and medium-protein grains (WG LP and WG MP), may be due to alteration in the mechanism of reaction in the DPPH method due to changes in phenolic concentration, as has been suggested previously [71]. Most of the phenolic compounds are located in the wheat bran layer covalently crosslinked with the cell wall polymers [49,69]; the phenolic content ratio in bran, as compared to germ, is 15-to 18-fold, as has been reported previously, and in agreement with different authors, this correspond mostly to phenolic acids [70].…”
Section: Total Antioxidant Capacity (Tac)supporting
confidence: 65%
“…Other authors have found a significant correlation between the antioxidant activity and total phenolic content in the albumin protein fraction in wheat [ 56 ]. The decrease in DPPH scavenging capacity of the WG HP-BP fraction, in relation to the low- and medium-protein grains (WG LP and WG MP), may be due to alteration in the mechanism of reaction in the DPPH method due to changes in phenolic concentration, as has been suggested previously [ 71 ].…”
Section: Resultsmentioning
confidence: 64%
“…In order to simplify the chemistry, we used a stable radical, 2,2′-diphenyl-1-picrylhydrazyl (dpph • , Figure 1 E), which is isoelectronic to peroxyls but is ∼3 orders of magnitude less reactive than alkylperoxyl radicals. Although the results of experiments with dpph • carried out in polar solvents cannot be directly extended on the peroxyl radicals, 14 careful analysis of the kinetics of the second order reaction with the radical-trapping agent, RTA provides valuable information on the role of polarity, kinetic solvent effects, and antiradical properties of RTAs as putative antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…RA, CA, and BA are thus negatively charged in the adsorption experimental conditions (pH < 7), so that attractive electrostatic interactions could drive their adsorption on the HAp surface. However, although BE is not fully deprotonated at pH 5 (first pKa for the phenol group is 5.5 ± 0.1 [ 53 , 54 ]), it is the most adsorbed polyphenol: on a molecular basis, BE was three times more adsorbed than BA, RA, and CA on HAp. This is consistent with a study by Chirdon et al [ 32 ] that showed that catechol and pyrogallol derivatives adsorbed more readily and strongly on HAp surfaces than phenol and carboxylic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the kinetics of the reaction for polyphenols in a polar solvent is fast, due to the participation of fast electron transfer in the mechanism of anti-radical activity [ 53 , 66 ], we can assume that the reaction reached its equilibrium for the four tested molecules in these conditions and we can link the anti-radical activity of the hybrid particles to their antioxidant properties. Furthermore, the concentration of polyphenols is very important as the mechanism is concentration-dependent [ 53 ]. Here, the anti-radical ability of hybrid particles was compared so that the concentration of particles in suspension was fixed.…”
Section: Discussionmentioning
confidence: 99%